The Origin of Systematic Forecast Errors of Extreme 2020 East Asian Summer Monsoon Rainfall in GloSea5. Issue 16 (25th August 2021) - Ham, Yoo‐Geun; Kim, Ji‐Gwang; Lee, Jeong‐Gil; Li, Tim; Lee, Myong‐In; Son, Seok‐Woo; Hyun, Yu‐Kyung
Abstract: This study examined the origin of the systematic underestimation of rainfall anomalies over East Asia during July–August 2020 in operational forecasts. Through partial nudging experiments, we found that the East Asian rainfall anomalies were successfully predicted in GloSea5 with corrected tropical sea surface temperature (SST) forcing. Once the observed SST is applied over the Indian Ocean and tropical central‐eastern Pacific, a low‐level anticyclonic anomaly over the subtropical western Pacific, which transports warm‐moist air from the tropics to increase the East Asian precipitation, is well reproduced as observed. By further separating the SST into climatological and anomalous components, we revealed that the cold and dry mean state bias over the Indian Ocean and central‐eastern Pacific is responsible for the weak anomalous atmospheric teleconnection patterns from the tropics to East Asia. This implies that correcting the model mean climatological fields can directly impact the operational seasonal forecast skill. Plain Language Summary: Adapting to destructive climate events based on successful forecasts is one way to reduce social and economic losses. Unfortunately, the operational rainfall forecasts during the summer of 2020 systematically underestimated the amount of rainfall anomalies over East Asia. Through partial nudging experiments, we found that East Asian rainfall anomalies were successfully predicted by correcting the tropical sea surface temperature (SST) forcing in the operational forecast system. The development of the anticyclonic flow anomalies over the subtropical western Pacific, which transport warm and wet air from the tropics and increase East Asian precipitation, could be accurately predicted once the observed SST is prescribed over the Indian Ocean and tropical central eastern Pacific in operational seasonal forecast system. Key Points: The operational rainfall forecasts during the summer of 2020 considerably underestimated the observed amount over East Asia The heavy rainfall over East Asia during 2020 summer is successfully predicted in GloSea5 by correcting tropical SST forcing The quality of simulated climatological SST fields impact the operational seasonal forecast skill